Predictors of relapse after improved ejection fraction in patients with heart failure. (25th November 2020) - Esteves, A.F; Marinheiro, R; Fonseca, M; Farinha, J.M; Pinheiro, A; Ferreira, J; Goncalves, S; Duarte, T; Fonseca, N; Caria, R
Abstract: Background: Patients with systolic dysfunction with improvement in left ventricular ejection fraction (LVEF) present a more favorable clinical profile when compared to those that maintain dysfunction. However, little is known about the characteristics of patients who "relapse" after LVEF improvement. Purpose: Evaluate prevalence, clinical characteristics and outcomes of patients in whom ejection fraction declined after previous improvement. Methods: We retrospectively studied patients followed at a heart failure (HF) clinic with LVEF improvement after an initial diagnosis of HF with reduced ejection fraction (EF), which was defined as having an LVEF >40% on follow-up. We then evaluated the presence of LVEF "relapse" in these patients – a decline in LVEF to <50% or <40%, in cases where it recovered to preserved EF or to mid-range EF, respectively. We analysed patient demographics, clinical parameters and outcomes and used logistic regression to assess the predictors of LVEF "relapse". Results: 98 patients were studied, 70 (71%) male, median age 69 (58–76) years. Fifty-four (55%) patients had recovered EF (>50%) and in 44 (45%) it had improved to mid-range values. In 36 (37%) occurred LVEF "relapse": in 10 (10%) patients to an EF 40–50% and in 88 (90%) to an EF<40%. Ischemic cardiomyopathy and non-ischemic dilated cardiomyopathy were the main HF aetiologies (38% and 35%, respectively). During a median follow-up of 7 years, 39 (40%) patients had at least one HF hospitalization. Global mortality was 30%, with no significant statistical difference between the two groups. In univariate analysis, HF duration, type 2 diabetes mellitus (T2DM), left main or left anterior descending coronary (LAD) disease, valvular heart disease (VHD) and chronic kidney disease (CKD) predicted LVEF "relapse". In multivariate analysis, T2DM, left main or LAD disease and VHD were the only predictors of LVEF "relapse" (Table). Conclusion: In this group of patients, LVEF "relapse" after it had initially improved was frequent and was predicted by the presence of T2DM, left main or LAD disease and VHD. Despite improved systolic function, these patients remain at high risk, thus the need to maintain treatment. Funding Acknowledgement: Type of funding source: None